Outcomes after first relapse of childhood intracranial ependymoma. Issue 8 (9th February 2021) - Tsai, Jessica W.; Manoharan, Neevika; Alexandrescu, Sanda; Zimmerman, Mary Ann; Scully, Jacqueline; Chordas, Christine; Clymer, Jessica; Wright, Karen D.; Filbin, Mariella; Ullrich, Nicole J.; Marcus, Karen J.; Haas‐Kogan, Daphne; et al.
Abstract: Background: Ependymoma is the third most common malignant CNS tumor in children. Despite multimodal therapy, prognosis of relapsed ependymoma remains poor. Approaches to therapy for relapsed ependymoma are varied. We present a single‐institution retrospective review of the outcomes after first relapse of intracranial ependymoma in children. Procedure: We performed a retrospective, IRB‐approved chart review of patients with recurrent intracranial ependymoma treated at Dana‐Farber/Boston Children's Cancer and Blood Disorders Center from 1990 to 2019. Results: Thirty‐four patients with relapsed intracranial ependymoma were identified. At initial diagnosis, 11 patients had supratentorial disease, 22 with posterior fossa disease and one with metastatic disease. Median time‐to‐first relapse was 14.9 months from initial diagnosis (range 1.4–52.5). Seven patients had metastatic disease at first relapse. Gross total resection (GTR) was associated with improved 5‐year progression‐free survival (PFS) relative to subtotal resection (STR) and no surgery ( p = .005). Localized disease at relapse was associated with improved 5‐year overall survival (OS) when compared to metastatic disease ( p = .02). Irradiation at first relapse seemed to delay progression but was not associated with statistically prolonged PFS or OS. Tumor location, histology, and chromosomal 1q status did not impact outcome at first relapse, although available molecular data were limited making definitive conclusions difficult. Median time‐to‐second relapse was 10 months (range 0.7–124). Five‐year PFS and OS after first relapse were 19.9% and 45.1%, respectively. Median PFS and OS were 10.0 and 52.5 months after first relapse, respectively. Conclusions: Relapsed intracranial ependymoma has a poor prognosis despite multimodal therapy. Novel therapeutic strategies are desperately needed for this disease.